INCIDENCES DE LA PLUVIOMETRIE SUR LA CULTURE DES CEREALES DANS LA STEPPE DU SUD DE LA PREFECTURE DE SIDI BEL’ABBES (ALGERIE OCCIDENTALE) - Hellal Tijania; Hellal Benchaben; Bardadi Abdelkader; Ayad Nadira; Bensmira Zaza (European Scientific Journal, ESJ, 2014)
The practice of cereals has increased due to the settlement of the nomadic population again and stagnation of sheep in the steppe of southern prefecture of Sidi Bel'Abbes Western Algeria. Given this situation it was intended to study the relationship between the production of cereals, rainfall and number of rainy days. The results show that grain production is dependent on the annual rainfall, spring rainfall and number of rainy days. Grain production has shown correlated with harvested despite the sharp decline in acreage plowed surface. Yields remain low and characterizing cereal crop grown for subsistence. Long periods of drought have acted negatively on production; only wadis and depressions were able to produce grain and straw to support livestock and Aboriginal Population